El asesinato (o la muerte en duelo) de Lope de Vega: escenas violentas de la vida del Fénix de los Ingenios - Sánchez Jiménez, Antonio (My University, 2026)
This article examines the instances in which Lope or his biographists evoke the possibility of his violent death.
Keywords: Lope de Vega; Violent Death; Golden Age Spanish Literature